A review of body composition and pharmacokinetics in oncology. Issue 9 (2nd September 2017) - Hopkins, Jessica J; Sawyer, Michael B
ABSTRACT: Introduction : Body surface area dosing of chemotherapeutic agents is based on limited scientific data, and often results in unpredictable plasma drug levels. Cross-sectional computed tomography (CT) imaging provides an accurate measurement of lean mass. This review summarizes emerging roles of lean mass in predicting pharmacokinetics and drug toxicities in cancer patients. Areas covered : A concise review of body composition measurement with CT cross-sectional imaging and its relationship to drug pharmacokinetics and toxicities. A comprehensive review of the predictive value of low lean mass (sarcopenia) in dose-limiting toxicities is also included. Expert commentary : Drug dosing in medical oncology faces many challenges, including heterogeneous body composition profiles. The emerging role of sarcopenia in predicting lean mass may provide the tool needed to more accurately dose patients and prevent dose-limiting toxicities.